OC21 Safe water versus normal saline nasophyrynx wash in the prevention of common cold among children: a stratified randomised control trial. (June 2019) - Khan, Faheem
Abstract : Introduction: Nasal rinsing with normal saline water is prescribe in paediatric practices in prevention of the upper respiratory infection (URTIs) in Pakistan. Safe water is not worse in effectiveness to normal saline effectiveness in nasophyrnx rinsing in primary prevention of common cold has not been established by trials. Methods: Double blind stratified randomized controlled trial carried out in August 2017-January 2018 winter season in Karachi, Pakistan. 774 healthy children aged 02 months to 5 years were included, randomly assigned to nasal wash with normal saline, safe water group at least 3 times a day followed-up 90 days. Features of URTIs recorded on check list. Per protocol analysis. Findings: 260 children contracted URTIs. Incidence rate of URTI was 0.52 episodes per 60 person days among control. Incidence rate decreased to 0.34 episodes per 60 person days in the safe water group and 0.48 episodes per 60 person days in the normal saline group. Non inferiority test value were 0.997 (90% CI=0.904–1.101). Safe water rinsing tended to decrease nasal symptoms (p=0.055). As hazard ratio=0.60, 95% CI=0.39–0.95 Innovations: Safe water rinsing was non inferior in effectiveness to normal saline in prevention of URTIs among healthy children. Safe water is cost effective modality would greater benefit the society.